2017
DOI: 10.1016/j.commatsci.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and diffusion at TiN/TiO2 interfaces: A first principles study

Abstract: This work uses density functional theory (DFT) calculations to analyze the energetics and stability of TiN/TiO 2 interfaces. Specifically, the work of adhesion and migration energy barriers for oxygen diffusion through the interface are calculated for multiple interface geometries and terminations. It is found that the stability of defect free interfaces is controlled by the work of adhesion because the migration energy barriers for oxygen across the interface are high in all cases. It is also found that the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To study MB adsorption, an optimized molecular structure was used [68]. The bulk of both ZnTiO 3 and TiO 2 crystals was cleaved on the surface (101), since it is the most stable surface according to the literature [54,57,62,66,82] An appropriate vacuum thickness of each structure was chosen by calculating the surface energy. For both ZnTiO 3 and TiO 2 surface models, a vacuum of 20 Å was added.…”
Section: Methodsmentioning
confidence: 99%
“…To study MB adsorption, an optimized molecular structure was used [68]. The bulk of both ZnTiO 3 and TiO 2 crystals was cleaved on the surface (101), since it is the most stable surface according to the literature [54,57,62,66,82] An appropriate vacuum thickness of each structure was chosen by calculating the surface energy. For both ZnTiO 3 and TiO 2 surface models, a vacuum of 20 Å was added.…”
Section: Methodsmentioning
confidence: 99%
“…While for TiO 2 on TiN (111), we use (001)‐oriented anatase‐TiO 2 due to the highest work of adhesion to TiN (111). [ 38 ] The potential energy surfaces describing TEMAH chemisorption on TiO x N y /TiN (100) and TiO 2 (001) are presented in Figure 3e,f, respectively. The calculations indicated that TEMAH reacted strongly with oxygen on the top surface in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 displays the interface structure of the Ge(111)/4H-SiC(0001) heterojunction based on the TEM characterizations [3]. The primitive cells of Ge(111) surface and 4H-SiC(0001) surface possess lattice constants of [01-1] Ge = 4.000Å, [11][12][13][14][15][16][17][18][19][20] SiC = 3.078Å. The lattice matching is 3 : 4 of Ge to SiC with a residual mismatch of 2.60% in the two parallel orientations using the smallest supercell mismatch.…”
Section: Resultsmentioning
confidence: 99%
“…All the calculations in this work were implemented by using the Cambridge Serial Total Energy Package (CASTEP) Code [12,13], which are based on the density functional theory (DFT) [14]. Generalized gradient approximation (GGA) of Perdew-Burke-Ernzerhof (PBE) scheme was employed to describe the exchange-correlation functional [15].…”
Section: Methodsmentioning
confidence: 99%